Kekuatan Eksekutorial Akta Perdamaian sebagai Alternatif Penyelesaian Sengketa Perdata di Luar Pengadilan - Kurdi, Kurdi; Cahyo, Raul Gindo; Dadek, Teuku Ahmad (JUNCTO: Jurnal Ilmiah Hukum, 2025)
This study analyzes the executorial power and effectiveness of peace deeds (dading) as an alternative instrument for resolving civil disputes outside the courts. Litigation still faces classic problems such as case backlogs, high costs, and lengthy processes, thus contradicting the principles of speedy and efficient justice. Peace deeds offer a peaceful solution, but there is a legal gap regarding their enforceability. This normative legal research finds a fundamental dualism: peace deeds through court mediation (in-court) that are confirmed as decisions have direct executorial power equivalent to a final and binding decision. Conversely, out-of-court peace deeds, even if made in an authentic notarial deed, do not have direct executorial power and only function as evidence, so that disputes over breach of contract must still be sued. The use of grosse akta for reciprocal dading is also legally inappropriate. In practice, the effectiveness of dading shows a paradox: the high number of requests for execution of peace deeds indicates low voluntary compliance and the shift of disputes to the execution stage. The main obstacle to the effectiveness of out-of-court dading is the lack of an execution mechanism in Law No. 30 of 1999. This study recommends amendments to the law to provide a registration mechanism and granting of execution fiat for out-of-court settlement deeds..